Demographic history shapes genomic variation in an intracellular parasite with a wide geographical distribution. Issue 9 (14th March 2022) - Angst, Pascal; Ebert, Dieter; Fields, Peter D.
Abstract: Analysing variation in a species' genomic diversity can provide insights into its historical demography, biogeography and population structure, and thus its ecology and evolution. Although such studies are rarely undertaken for parasites, they can be highly revealing because of the parasite's co‐evolutionary relationships with hosts. Modes of reproduction and transmission are thought to be strong determinants of genomic diversity for parasites and vary widely among microsporidia (fungal‐related intracellular parasites), which are known to have high intraspecific genetic diversity and interspecific variation in genome architecture. Here we explore genomic variation in the microsporidium Hamiltosporidium, a parasite of the freshwater crustacean Daphnia magna, looking especially at which factors contribute to nucleotide variation. Genomic samples from 18 Eurasian populations and a new, long‐read‐based reference genome were used to determine the roles that reproduction mode, transmission mode and geography play in determining population structure and demographic history. We demonstrate two main Hamiltosporidium tvaerminnensis lineages and a pattern of isolation‐by‐distance, but note an absence of congruence between these two parasite lineages and the two Eurasian host lineages. We suggest a comparatively recent parasite spread through Northern Eurasian host populations after a change from vertical to mixed‐mode transmission and the loss of sexual reproduction. While gaining knowledge about the ecology and evolution of this focal parasite, we also identify common features that shape variation in genomic diversity for many parasites, such as distinct modes of reproduction and the intertwining of host–parasite demographies.